Perencanaan Turbin Air untuk Pembangunan Pembangkit Listrik Tenaga Minihidro (PLTM) Warnasi di Kab. Manokwari, Papua Barat - Erma Yuniaty; Muhammad Syahfriandi (JURNAL TEKNIK MESIN, 2026)
The demand for electricity in the Manokwari Regency, West Papua Province, continues to increase year by year. However, the limited number of power plants and the region’s heavy reliance on diesel-based power plants (PLTD) remain major obstacles to supporting the region’s development and progress.To meet the growing electricity needs and support the government’s program in utilizing non-fossil energy resources, the development of power plants based on New and Renewable Energy (NRE) has become a viable solution. Among the renewable energy options, hydropower and solar energy are particularly promising for development in the Manokwari region due to their abundant and sustainable availability.Hydropower is considered highly suitable for development in Manokwari, given the area's topographical characteristics and sufficient water resources. Therefore, the aim of this study is to plan and design a water turbine as part of the development of a Mini Hydro Power Plant (PLTM) to support the government’s NRE initiatives.One of the most promising sites for PLTM development is the Warnasi River, which has a watershed area (DAS) of approximately 117.75 km² and an average river discharge of 8.26 m³/s. Based on field surveys conducted in the Warnasi River, the flow conditions are deemed adequate for the construction of a mini-hydro power plant.In designing the water turbine, the initial step is to determine the appropriate type of turbine by analyzing its efficiency based on key parameters such as head and discharge. Subsequently, calculations are conducted to determine the turbine’s power output, rotational speed limits, and the main dimensions of the turbine. These design and calculation processes will be discussed in detail in this final project as part of the technical planning for the hydropower system development in the Warnasi River